Effects of the contraceptive pill on sedative responses to clonidine and apomorphine in normal women. - Chalmers, J; Fulli-Lemaire, I; Cowen, P (1985)
In normal women sedation following intravenous administration of the alpha 2-adrenoceptor agonist clonidine (1.3 micrograms/kg) was significantly greater following 3 weeks' continuous treatment with the combined contraceptive pill than at the end of the 7-day withdrawal period. In contrast, sedative responses to the dopamine agonist apomorphine (5 micrograms/kg subcutaneously) were decreased when subjects were taking the contraceptive pill. These findings are in agreement with animal experimental studies, indicating that oestrogen can alter alpha-adrenoceptor and dopamine autoreceptor sensitivity. Such interactions may be involved in the effects of female sex steroids on mood.